(untitled) (UUM Journal of Legal Studies, 2016)
The end of the cold war and the beginning of the new millennium brought with it a new phase in state relations in Africa as more persons became forcefully uprooted from their homes and their rights violated with impunity due to intractable internal conflicts amidst the Westphalian notion of sovereignty which frowns at interference in the internal affairs of any state which was the fulcrum upon which the United Nations (UN) and Organization of African Unity (OAU) was founded. This new awakening has increasingly made perception of sovereignty to be people oriented. In the case of the Africa which is the crux of this paper, the eventual change from OAU to AU was significant as the coming into force of African Unionâ€™s Constitutive Act and the Convention for the Protection and Assistance of Internally Displaced Persons climaxed major twist in the Africaâ€™s perception of sovereignty and the right of intervention in relation to internally displaced persons (IDPs) within the continent. This article examines briefly the historical evolution of the concept of sovereignty and the right of intervention and their implications in the African context, and being conceptual and doctrinal in approach it analyses the context and legality of the African Unionâ€™s right of intervention arising from the regional treaties vis-Ã -vis the United Nations Charter with a view to vindicating the much celebrated â€˜decisive break from the pastâ€™. It concludes that African Unionâ€™s current stance represents a bold and grandiose expression that is sincerely tailored towards ensuring effective human rights protection and humanitarian assistance for over 13 million internally displaced persons (IDPs) in Africa. Finally, the article contributes significantly to the scholarly debates surrounding right of intervention in relation to internal displacement as its resolution will in one or the other helps government and other stakeholders in their quest to curtail the scourge of intra and inter-state violence in Africa. Keywords: African Union, Sovereignty, Intervention, Internally Displaced Persons, State Responsibility